Preface - Committee, The Organizing (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
During the period September 17-20, 2014, the third edition of the InternationalConference on Numerical Analysis and Approximation Theory (NAAT 2014) was heldat Babes-Bolyai University of Cluj-Napoca, Romania. Previous editions have takenplace in July 2006 and September 2010.